PERENCANAAN MANAJEMEN PROYEK KONSTRUKSI PEMBANGUNAN GEDUNG PARKIR KEPOLISIAN RESORT KOTA SINGKAWANG: PERENCANAAN MANAJEMEN PROYEK KONSTRUKSI PEMBANGUNAN GEDUNG PARKIR KEPOLISIAN RESORT KOTA SINGKAWANG - Aulia, Rahayu; Syafriadi, syafriadi; Iswani, Shilvi (RETENSI, 2023)
Construction Project Management plays an important role in the construction of a building from the beginning of the building until finally the building is ready for occupancy. The parking building is one of the facilities provived by the Singkawang City police resort which aims to accommodate motorized vehicles effectively and efficiently within the Singkawang City police resort. To realize this development, careful planning is needed, so as not to cause problems that harm various parties, in order to create effective and efficient planning, Construction Project Management is the right solution asa a solution to this problem. The results of this plan aim to build a parking building at the Singkawang City police resort. In this paper, present calculations and estimates of costs, time, human resouces, occupational safety and health and quality management systems to support the planning process of building parking facilities in Singkawang City police resort environment.